2021
DOI: 10.3389/fpsyg.2021.716529
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Histories Facilitating the Emergence of Creative Scientific Expertise: The Role of Developed Cognitive Talents, Education, and Social and Cultural Contexts

Abstract: Understanding how individual and contextual factors collectively contribute to the developmental histories that facilitate the emergence of creative expertise in science is improved by considering the contribution of the broad structure of developed cognitive abilities to creativity, prospective research on the high achieving or gifted students who may choose careers in and end up as creative scientists later in life, as well as retrospective studies of established creative scientists themselves and what their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…For example, Lewis Terman’s work in California and the Scottish Mental Survey both illustrated a positive correlation between IQ and longevity ( Deary et al 2008 ; Holahan 2021 ). Wai and Brown ( Wai and Brown 2021 ) using a sample of 48,558 individuals from the US and the UK found that cognitive ability in youth correlated with several positive outcomes in educational, health, social, and occupational attainments. Moreover, the contributions of genetic influences to measured IQ scores appear to increase with age; this may suggest that school-based programming has more influence on younger learners, a view that would support the effectiveness of gifted education and other school-based interventions, or perhaps there are selection effects, motivational differences, or other extraneous variables that influence this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lewis Terman’s work in California and the Scottish Mental Survey both illustrated a positive correlation between IQ and longevity ( Deary et al 2008 ; Holahan 2021 ). Wai and Brown ( Wai and Brown 2021 ) using a sample of 48,558 individuals from the US and the UK found that cognitive ability in youth correlated with several positive outcomes in educational, health, social, and occupational attainments. Moreover, the contributions of genetic influences to measured IQ scores appear to increase with age; this may suggest that school-based programming has more influence on younger learners, a view that would support the effectiveness of gifted education and other school-based interventions, or perhaps there are selection effects, motivational differences, or other extraneous variables that influence this relationship.…”
Section: Discussionmentioning
confidence: 99%